A nationwide 16-year study of the trends, burden and impact of atrial fibrillation in cardiac amyloidosis. (25th November 2020) - Isath, A; Perembeti, S; Ho, K; Correa, A; Haider, S.W; Siroky, G; Narasimhan, B; Padmanabhan, D; Mehta, D
Abstract: Background: Cardiac amyloidosis (CA) remains an underdiagnosed entity. Atrial fibrillation (AF) is common in patients with CA, likely owing to direct amyloid deposition in the left atrium. However, the prevalence of AF in CA and its association with in-hospital outcomes has not been studied in large populations. Purpose: Our aim was to study the trends, baseline characteristics, and clinical impact of AF in patients with CA in the United States using the Healthcare Cost and Utilization Project (HCUP) National) Inpatient Sample (NIS) from 1999 to 2014. Methods: We queried the NIS and identified CA using ICD-9-CM codes 277.39 and 425.7. AF in CA patients was identified using the ICD-9-CM code of 427.31. Statistical Analysis System (SAS) 9.4 was used for analysis of data. Results: There were a total of 145, 920 CA hospitalizations between 1999 and 2014 in the United States, of which 37, 070 (25.4%) had AF. The prevalence of AF remained consistent from 27.5% in 1999 to 27.4% in 2014. The mean age of patients with AF was 72.9±28.2 years and for patients without AF was 67±31.9 years (p<0.0001). The majority of the patients with AF were male (60.3%) and the study group was predominantly white (62.8% in patients with AF and 56.4% in patients without AF). CA patients with AF suffered more from thyroid-related disease (22.5% vs 16.1%), heart failure (62.9% vs 36.5%) and renal failure (34.7% vs 30.5%) and less from hypertension (29.3% vs 34.0%) and diabetes mellitus (23.2% vs 25.2%) (p<0.0001). There was no significant difference in the Charlson comorbidity score between the groups. Inpatient mortality was significantly higher in CA patients with AF (10.4% vs 6.5%, p<0.001). However, in-patient mortality has been decreasing over the years from 10.3% in 1999 to 7.6% in 2014. Furthermore, cardiogenic shock was significantly higher in CA patients with AF (2.1% vs 1.2%, p<0.001), yet the use of mechanical circulatory support was not significantly different between the groups (0.42% vs 0.35%, p=0.375). Pacemaker implantation was also noted to be higher in CA patients with AF compared to patients without AF (2.8% vs 1.2%, p<0.0001). There was no significant difference between CA patients with and without AF in mean cost of hospitalization (58222±10752 vs 57695±545, p=0.081) or length of stay (7.9±0.1 vs 7.7±0.1 days, p=0.7089). Conclusion: CA with atrial fibrillation is a well-recognized entity, and our large scale retrospective analysis found significant association with worse in-hospital outcomes and cardiogenic shock. Interestingly, trend of in-patient mortality in CA has been decreasing over the years, likely owing to improved imaging modalities for diagnosis. Optimal management of AF in CA is imperative to improve outcomes in this population. Funding Acknowledgement: Type of funding source: None